Optimization of aluminum dopant amalgamation immersion time on structural, electrical, and humidity-sensing attributes of pristine ZnO for flexible humidity sensor application - Mamat, Mohamad Hafiz; A Subki, A Shamsul Rahimi; Mohamed Zahidi, Musa; Abdullah, Mohd Hanapiah; Shameem Banu, Itreesh Basha; Vasimalai, Nagamalai; Ahmad, Mohd Khairul; Nayan, Nafarizal; Abu Bakar, Suriani; Mohamed, Azmi; Birowosuto, Muhammad Danang; Mahmood, Mohamad Rusop (MDPI, 2022)
This study synthesized pristine and aluminum (Al)-doped zinc oxide (Al:ZnO) nanostructures through a simplistic low-temperature ultrasonicated solution immersion method. Al:ZnO nanostructures were synthesized as a sensing material using different immersion times varying from two to five hours. The Al:ZnO nanostructured-based flexible humidity sensor was fabricated by employing cellulose filter paper as a substrate and transparent paper glue as a binder through a simplistic brush printing technique. XRD, FESEM, HRTEM, EDS, XPS, a two-probe I–V measurement system, and a humidity measurement system were employed to investigate the structural,morphological, chemical, electrical, and humidity-sensing properties of the pristine ZnO and Al:ZnO nanostructures. The structural and morphological analysis confirmed that Al cations successfully occupied the Zn lattice or integrated into interstitial sites of the ZnO lattice matrix. Humidity-sensing performance analysis indicated that the resistance of the Al:ZnO nanostructure samples decreased almost linearly as the humidity level increased, leading to better sensitivity and sensing response. The Al:ZnO-4 h nanostructured-based flexible humidity sensor had a maximum sensing response and demonstrated the highest sensitivity towards humidity changes, which was noticeably superior to the other tested samples. Finally, this study explained the Al:ZnO nanostructures-based flexible humidity sensor sensing mechanism in terms of chemical adsorption, physical adsorption, and capillary condensation mechanisms.